Critical approaches to Cypriot and wider Mediterranean archaeology (Bristol)
xii, 351 sayfa
Keywords: “This volume brings together scholars to reflect on the work of Professor A. Bernard Knapp and on some of the challenges thrown down in his extensive scholarship. Knapp is a central figure in the pre- and proto-history of the Mediterranean in the last generation, and the essays in this volume will be of interest and attention to a wide range of scholars and students of Mediterranean pre- and proto-history. The authors comprise a mixture of senior, mid-career, and rising junior scholars - from various backgrounds, in order to offer a broad range of perspectives on the state and future of the archaeology of Cyprus and the wider Mediterranean.“ --